Privacy revisited : a global perspective on the right to be left alone - Krotoszynski, Ronald J., 1967- (New York, NY : Oxford University Press, 2016)
'Privacy Revisited' articulates the legal meanings of privacy and dignity through the lens of comparative law, and argues that the concept of privacy requires a more systematic approach if it is to be useful in framing and protecting certain fundamental autonomy interests.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: Privacy, Right of; Law; Laws of specific jurisdictions & specific areas of law